2007
DOI: 10.2741/2353
|View full text |Cite
|
Sign up to set email alerts
|

Chemical structure and immunobiological activity of Porphyromonas gingivalis lipid A

Abstract: In 1933, Boivin et al. extracted an endotoxin from Salmonella typhimurium for the first time, after which a variety of chemical and biological studies on endotoxins have been performed. In 1952, the structural and functional properties of endotoxic lipopolysaccharide (LPS), extracted by a hot phenol and water method devised by Westphal et al., were reported, which led to a number of studies of Gram-negative bacteria in regards to the host defense mechanism. Since 1960, the unique chemical structure and biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 85 publications
0
77
0
Order By: Relevance
“…In contrast to the LPS produced by a majority of Gram-negative bacteria, which binds to TLR4 (34), P. gingivalis LPS is known to activate TLR2 (35,36). This may be derived partly from the chemical structure of P. gingivalis lipid A, the bioactive moiety of LPS, which differs remarkably from lipid A produced by enterobacteria, such as Escherichia coli (37).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to the LPS produced by a majority of Gram-negative bacteria, which binds to TLR4 (34), P. gingivalis LPS is known to activate TLR2 (35,36). This may be derived partly from the chemical structure of P. gingivalis lipid A, the bioactive moiety of LPS, which differs remarkably from lipid A produced by enterobacteria, such as Escherichia coli (37).…”
Section: Discussionmentioning
confidence: 97%
“…P. gingivalis is a common oral bacterium that has been extensively characterized for its ability to promote gingival tissue and alveolar bone destruction. P. gingivalis LPS has been reported to use either TLR4 or TLR2 in its signaling, 19,[23][24][25] and Shapira et al reported that injecting whole killed P. gingivalis bacteria into subcutaneous chambers in SJL mice resulted in enhancement of EAE. 26 In contrast to these studies that used whole bacteria or P. gingivalis LPS, our studies focused on uniquely structured, non-LPS lipids produced by P. gingivalis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides ␣-glucan, many structurally unrelated compounds, including various glycolipids, lipopeptides, proteins, and polysaccharides, have been shown to induce TLR2 activation (25,52). However, despite the sometimes convincing evidence, the activity of many of these compounds was later on shown to be caused by contamination with lipopeptides (53)(54)(55). To investigate the possibility that the observed TLR2-stimulating activity of ␣-glucan was caused by lipopeptide contamination, ␣-glucan was pretreated with hydrogen peroxide, phenol, and amyloglucosidase and retested for the activity on HEK293 TLR2 cells.…”
Section: Mycobacterial ␣-Glucan Is Not a Ligand For Tlr2mentioning
confidence: 99%